THE IMPACT OF CASH RATIO, DEBT TO EQUITY RATIO, RECEIVABLES TURNOVER, NET PROFIT MARGIN, RETURN ON EQUITY, AND INSTITUTIONAL OWNERSHIP TO DIVIDEND PAYOUT RATIO - AFFANDI, FAKHRUN; SUNARKO, BAMBANG; YUNANTO, ARY (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this research is to know the influence of cash ratio, DER, recivable turnover, NPM, ROE, and institutional ownership on dividend payout ratio at manufacturing company. This research was conducted at manufacturing company listed in BEI period 2011 until 2016. The sampling technique used is purposive sampling, which is a sample of 19 companies. Data analysis in this study using classical test, multiple linear regression analysis, F test, adjusted R square, and t test. From the results of the research is known that receivables turnover, return on equity, and institutional ownership have a significant positive effect on dividend payout ratio. While the rest, cash ratio, DER, and NPM did not significantly affect the dividend payout ratio in manufacturing companies in 2011-2016.